Perspectives of the Use of ChatGPT as a Tool for Online Education of English - Pokotylo, Pavlo (Educological discourse, 2023)
Online education has become increasingly popular over the years, especially in Ukraine. It is determined by set of factors connected with COVID pandemic situation and war that caused disruptions to the traditional classroom settings. In recent years, artificial intelligence (AI) has been implemented for language teaching through chatbots, as well as language models like Google’s BERT and OpenAI’s GPT, which can generate text based on different informational background. With the rapid grows of the remote learning and online education, it is essential that educational institutions start to use innovative technologies such as ChatGPT to enrich students learning experience. Globalization process and democratic changes in Ukraine have a great impact on the education. Ukraine as fast grooving and developing democratic European country catches up with the European system of education. ChatGPT can be considered as controversial educational tool. This research defines terms chatbot, AI, ChatGPT, online education, distance learning. It is to give some of current results as well as possible perspectives of use of ChatGPT as modern tool for online Education in the sphere of English language. ChatGPT can make online-education more productive for both lecturers and students. ChatGPT can be used for personalized content regarding any criteria that could be insert to modify its settings, with guidance and real time interaction. At the same time use of ChatGPT for online education with students without proper level of English or without their teacher support can lead to negative consequences. Ukraine can take all of the best from European online educational experience and even improve distance learning on the national background. Use of the advanced technologies makes remote learning possible